2020
DOI: 10.1063/5.0010509
|View full text |Cite
|
Sign up to set email alerts
|

Water mediated electron attachment to nucleobases: Surface-bound vs bulk solvated electrons

Abstract: We have investigated the electron attachment dynamics of uracil in water using accurate wavefunction and QM/MM methods. The initial electron attached state is found to be localized on the water and mixing of electronic and nuclear degrees of freedom leads to the transfer of electron from the water to the uracil. The water molecules around the uracil stabilize the uracil bound anion by creating an extensive hydrogen-bonding network. The presence of the bulk water environment accelerates the rate of electron att… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 74 publications
2
44
0
Order By: Relevance
“…Figure 11 shows the EA-EOM-DLPNO-CCSD natural orbitals corresponding to the anionic states localized on water and cytosine for the first few snapshots from the first QM/MM trajectory (taken after 1ns of classical MD run). We have previously shown that the initial water-bound states of nucleobases arise primarily due to the interaction of the electron with bulk water 56 . The anionic states localized on the cytosine starts to appear within 5.5 fs of the initial electron attachment.…”
Section: Mechanism Of Electron Attachment In Bulk Watermentioning
confidence: 99%
“…Figure 11 shows the EA-EOM-DLPNO-CCSD natural orbitals corresponding to the anionic states localized on water and cytosine for the first few snapshots from the first QM/MM trajectory (taken after 1ns of classical MD run). We have previously shown that the initial water-bound states of nucleobases arise primarily due to the interaction of the electron with bulk water 56 . The anionic states localized on the cytosine starts to appear within 5.5 fs of the initial electron attachment.…”
Section: Mechanism Of Electron Attachment In Bulk Watermentioning
confidence: 99%
“…The last set of molecules consists of mono-hydrated nucleobases. The aqueous environment plays a crucial role in the biological functions of DNA and RNA [7,29,100]. Therefore, we have included the lowest energy mono-hydrated isomers of the five nucleobases.…”
Section: Description Of the Benchmark Setmentioning
confidence: 99%
“…A large number of theoretical studies on the calculation of IP and Electron Affinity (EA) values of genetic materials have been described in the literature [18][19][20][21][22][23][24][25][26][27][28][29][30]. A wide variety of methods such as semi-empirical methods, Hartree-Fock theory [31], density functional theory (DFT) [32,33], coupled cluster method [34][35][36], MP2 [37], Green's function-based approaches [38][39][40], Algebraic diagrammatic construction (ADC) [40][41][42][43], equation of motion coupled cluster (EOM-CC) method and the state-of-the-art multi-reference wave-function based methods [44][45][46] have been used for these calculations.…”
Section: Introductionmentioning
confidence: 99%
“…To check the accuracy and efficiency of the multilayer EA-EOM-DLPNO-CCSD method we have chosen a monohydrated uracil system as a simple test case. The initially optimized anion-geometry has been taken from ref 112 . The multilayer EA-EOM-DLPNO-CCSD method is an approximation to the standard EA-EOM-DLPNO-CCSD method.…”
Section: Microsolvated Uracilmentioning
confidence: 99%